2019
DOI: 10.1186/s12885-019-6265-1
|View full text |Cite
|
Sign up to set email alerts
|

Radiological appearance of hepatocellular carcinoma predicts the response to trans-arterial chemoembolization in patients undergoing liver transplantation

Abstract: BackgroundThe ultimate goal of locoregional therapy (LRT) to the liver is to induce total tumor necrosis. Trans-arterial chemoembolization (TACE) is the mainstay bridging therapy for patients with hepatocellular carcinoma (HCC) waiting for liver transplantation (LT). However, tumor response rate is variable. The purpose of this study was to correlate HCC radiological appearance with level of tumor necrosis during explant analysis from patients undergoing LT who received pre-LT TACE.MethodsFrom January 2000 to … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 33 publications
3
11
1
Order By: Relevance
“…Several studies aimed to find predictive preoperative imaging biomarkers for early CR of HCC after chemoembolization. Our results confirmed the findings by Zhang et al [11] and Vesselle et al [10], about smooth margins and smaller size of the lesions being good predictors of higher susceptibility to TACE. In a previously published surgical series [28], HCC nodules without smooth margins showed a higher rate of histopathologic proven microvascular invasion which can explain, at least in part, their lower CR rate.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…Several studies aimed to find predictive preoperative imaging biomarkers for early CR of HCC after chemoembolization. Our results confirmed the findings by Zhang et al [11] and Vesselle et al [10], about smooth margins and smaller size of the lesions being good predictors of higher susceptibility to TACE. In a previously published surgical series [28], HCC nodules without smooth margins showed a higher rate of histopathologic proven microvascular invasion which can explain, at least in part, their lower CR rate.…”
Section: Discussionsupporting
confidence: 93%
“…Our data showed an overall CR rate of 49.6%, in line with those reported in other per-lesion analyses [11,13,27]. Vesselle et al reported an overall CR rate of 26% [10]; it is to note, however, that their CR rate increased to 39% for lesions ≤ 5 cm.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations